Knowledge, attitude, and determinants of exclusive breastfeeding during COVID-19 pandemic among lactating mothers in Mekelle, Tigrai: a cross sectional study - Gebretsadkan Gebremedhin Gebretsadik; Zuriash Tadesse; Liya Mamo; Amaha Kahsay Adhanu; Afework Mulugeta (BMC, 2022)
Abstract Background Due to the nutritive and immunologic benefits of breastmilk, children should be exclusively breastfed for the first 6 months of life, even during the corona virus pandemic. However, fear of transmission risk and pandemic-related restrictions could undermine the practice of breastfeeding. This study aimed to assess the knowledge, attitude, and determinants of exclusive breastfeeding (EBF) during COVID-19 among lactating mothers in Mekelle, Tigrai, Ethiopia. Methods A community based cross-sectional study was conducted among 621 lactating mothers living in Mekelle city, Tigrai, from April to June, 2021. Data were collected using an adapted form of a standard KAP questionnaire. Binary logistic regression was used to determine the independent determinants of EBF at a statistical significance of p < 0.05. The strength of the association was measured by odds ratio and 95% confidence interval. Results Four hundred (64.4%) mothers exclusively breastfed their children. Infants from female-headed households had twice (AOR 2.21; 95% CI 1.31, 3.71) higher odds of EBF. Higher educational status was associated with higher odds of EBF practice. A unit increase in parity was associated with a 23% increase in the odds of EBF. Mothers who received breastfeeding information had a 73% (AOR 1.73; 95% CI 1.17, 2.56) higher odds of EBF. Moreover, mothers with high knowledge score and positive attitude showed a 74% higher (AOR 1.74; 95% CI 1.20, 2.51) and more than double (AOR 2.35; 95% CI 1.50, 3.70) odds of EBF, respectively. Conclusion About two-thirds of the mothers practiced EBF. Household head, maternal educational, parity, breastfeeding information, knowledge of breastfeeding, and attitude towards EBF were significant determinants of EBF. Our study findings highlighted that programs that enhance women's participation in education and decision-making could improve EBF practice. Besides, during the COVID-19 pandemic, providing lactating mothers with adequate and up-to-date breastfeeding information could be significant in improving EBF practice.